Analisis Yuridis Penyimpanan Minuta Akta Notaris Secara Elektronik - Thea Farina Embang; Elin Sudiarti (LPPM Universitas Ekasakti Padang, 2023)
Several studies explain that there is overlap between the duties of a notary and electronic storage of notarial deeds which is very rare in Indonesia. Using a digital-based deed, such as the minutes of an electronic notary deed, is still difficult to accept. This study aims to look at the study of juridical law enabling fast-paced information technology to be utilized to digitize minutes of notarial deeds. This approach is a qualitative study based on normative legal procedures. Based on the findings, using minutes of notarial deeds electronically is not yet possible in Indonesia at this time.